THE EXISTENCE AND ROLE OF FEMALE WEAVERS OF MALE SARONGS (RAGI) IN DEVELOPING THE POTENTIAL OF LOCAL PRODUCTS AS A SOURCE OF CREATIVE ECONOMY IN WOZOKARO VILLAGE, ROWORENA BARAT SUBDISTRICT, ENDE REGENCY: Eksistensi Dan Peran Perempuan Penenun Sarung Laki-Laki (Ragi) Dalam Mengembangkan Potensi Produk Lokal Sebagai Sumber Ekonomi Kreatif Di Kampung Wozokaro Kelurahan Roworena Barat Kabupaten Ende - Yosef Dentis; Herkulianus Wae Tawa; Yohanes Eudes Go (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the existence and role of female weavers of male sarongs (ragi) in developing the potential of local products as a source of creative economy in Wozokaro Village, Roworena Barat Subdistrict, Ende Regency. Female weavers play a strategic role as cultural preservers as well as drivers of the creative economy through the production of distinctive and high-value ragi sarongs. The research employed a descriptive qualitative method with a field study approach, including participatory observation, in-depth interviews, and documentation of production processes, design innovations, and product marketing. The results indicate that female weavers not only maintain local traditions but also enhance product quality, create innovative designs, and expand marketing networks. These activities contribute significantly to the economic empowerment of the local community while establishing ragi sarongs as superior products with both cultural and economic value. The study concludes that the existence and role of female weavers of male sarongs are crucial in developing the creative economy potential of local products, serving as a model for community empowerment and cultural preservation at both local and regional levels.-